New original metabolitotropic endothelioprotector "Angiolin": quantum-chemical parameters and peculiarities of pharmacological action - Chekman, I.S.; Kazakova, O.A.; Mazur, I.A.; Nagornaya, E.A.; Belenichev, I.F.; Gorchakova, N.A.; Buhtiyarova, N.V.; Syrova, A.O.; Dovhan, R.S.; Zahorodnyi, M.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
By means of the density functional theory with the use of the solvation model IEF PCM, the electronic and energetic properties of "Angiolin" are researched. It is established that the equilibrium structure with the lowest level of Gibbs free energy is stabilized by intramolecular oxygen bonds, and the main reaction centers are ionic groups, the groups participating in H- bonds and the heterocycle of thiotriazoline.